2020
DOI: 10.1093/milmed/usaa011
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Musculoskeletal Injuries and the Canadian Armed Forces Physical Employment Standard Proxy in Canadian Military Recruits

Abstract: Introduction Musculoskeletal injuries (MSKIs) and recruitment are major challenges faced by modern military forces. The Canadian Armed Forces uses a physical employment standard (PES) proxy to determine occupational fitness and job suitability. It is unknown whether the performance on the PES proxy can be also used as predictor of MSKIs. The purpose of this study was to investigate for relationships between age, sex, body composition, aerobic fitness, performance on the Canadian Armed Forces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
7
0
3
Order By: Relevance
“…Lower pre-BMT levels of muscular strength and endurance [ 17 , 21 ] and cardiorespiratory fitness [ 8 , 17 , 20 ], have been associated with a greater risk of injury in recruits. In support of this previous research, the current investigation similarly found that lower baseline cardiorespiratory fitness and muscular fitness were associated with a higher risk of injury during BMT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower pre-BMT levels of muscular strength and endurance [ 17 , 21 ] and cardiorespiratory fitness [ 8 , 17 , 20 ], have been associated with a greater risk of injury in recruits. In support of this previous research, the current investigation similarly found that lower baseline cardiorespiratory fitness and muscular fitness were associated with a higher risk of injury during BMT.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk factors have been consistently identified that predict premature attrition and injury during BMT, with these factors often overlapping across both adverse outcomes. These include sustaining a musculoskeletal injury during training [ 12 , 13 , 14 ], injury history prior to military training [ 15 , 16 , 17 , 18 , 19 ], lower levels of muscular strength and endurance [ 8 , 12 , 13 , 17 , 19 , 20 , 21 ], and demographic factors such as older age [ 19 , 22 ], female sex [ 13 , 18 , 22 ], lower education level [ 12 , 15 ], and smoking status [ 13 , 14 ]. However, these risk factors are typically only measured once, at recruit entry to BMT.…”
Section: Introductionmentioning
confidence: 99%
“…Debido a lo anterior, el acondicionamiento físico es el pilar fundamental que requiere un militar para poder desempeñar las labores propias de su profesión, para ello el entrenamiento básico y los cursos militares específicos, se tienen que caracterizar por brindar un mejoramiento significativo de las capacidades de la condición física incluyendo su composición corporal, la adaptación aeróbica y anaeróbica al ejercicio, la fuerza muscular del tren superior e inferior, la agilidad, la potencia y resistencia muscular (Chassé et al, 2020;Hazell et al, 2010;Hendrickson et al, 2010).…”
Section: Introductionunclassified
“…Con el mejoramiento de la composición corporal se logra un aumento en la efectividad para el cumplimiento de las tareas militares y con ello se alcanza una reducción del número de lesiones por el sobrepeso (Smith et al, 2012). La evaluación de variables como la circunferencia de cintura, así como de la predicción del consumo máximo de VO2, determinan información valiosa del progreso de los planes de entrenamiento en reducir el riesgo de enfermedades cardiovasculares y mejorar tanto los componentes del acondicionamiento y en definitiva del estado de salud del militar (Chassé et al, 2020). Por otro lado, el nivel de condición física y la determinación de la antropometría del individuo que se ve sometido a cargas de peso, son factores importantes para el tipo de actividad militar.…”
Section: Introductionunclassified
See 1 more Smart Citation